Determinan Kinerja Keuangan Perusahaan - Mujiyati, M; Susilowati, Kartiningsih (Prosiding University Research Colloquium, 2020)
This research aims to determine the influence of the board of directors, board of commissioners, audit committee, and company size to the company’s financial performance. The sample used in this research were 53 manufactur companies sub-sector food and beverage listed on Indonesia Stock Exchange (BEI) period 2014 to 2018. The sampling method uses purposive sampling method. The analysis in this research uses the method of multiple linear analysis. The results of this research can be seen that the board of directors, board of commissioners, and company size have influence to the company’s financial performance. While the audit committee have no influence to the company’s financial performance.